1971
DOI: 10.1128/jb.108.1.400-409.1971
|View full text |Cite
|
Sign up to set email alerts
|

Phenylalanine and Tyrosine Biosynthesis in Escherichia coli K-12: Mutants Derepressed for 3-Deoxy- d -Arabinoheptulosonic Acid 7-Phosphate Synthetase (phe), 3-Deoxy- d -Arabinoheptulosonic Acid 7-Phosphate Synthetase (tyr), Chorismate Mutase T-Prephenate Dehydrogenase, and Transaminase A

Abstract: Mutant strains of Escherichia coli have been isolated in which the synthesis of 3deoxy-D-arabinoheptulosonic acid 7-phosphate (DAHP) synthetase (phe) is derepressed, in addition to those enzymes of tyrosine biosynthesis previously shown to be controlled by the gene tyrR. The major enzyme of the terminal pathway of phenylalanine biosynthesis chorismate mutase-prephenate dehydratase is not derepressed in these strains. Genetic analysis of the mutants shows that the mutation or mutations causing derepression map … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1973
1973
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Effect of mutations in the regulator genes trpR and tyrR on the synthesis of shikimate kinase. Both tryptophan and tyrosine, in concert with the product of the regulator genes trpR and tyrR, respectively, are involved in the repression of other enzymes of aromatic biosynthesis in E. coli (7,17,21,28,31,32,34). To test whether the product of either the trpR or tyrR gene is also involved in the repression of shikimate kinase, enzyme levels were measured in mutant strains in which one or other of the regulator gene products was nonfunctional.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of mutations in the regulator genes trpR and tyrR on the synthesis of shikimate kinase. Both tryptophan and tyrosine, in concert with the product of the regulator genes trpR and tyrR, respectively, are involved in the repression of other enzymes of aromatic biosynthesis in E. coli (7,17,21,28,31,32,34). To test whether the product of either the trpR or tyrR gene is also involved in the repression of shikimate kinase, enzyme levels were measured in mutant strains in which one or other of the regulator gene products was nonfunctional.…”
Section: Resultsmentioning
confidence: 99%
“…Assay of chorismate mutase. The method described by Im et al (17) was used to assay chorismate mutase.…”
Section: Methodsmentioning
confidence: 99%
“…)phan in phenylal-Effect of a tyrR mutation on transport JC411, the strain regulation. The tyrR gene has been shown to ived, did show en-code for an aporepressor that is involved in the tophan (data not control of the expression of at least four differhe increased activent genetic loci concerned with aromatic bioinvolves the previ-synthesis (8,10,13,24; Ely and Pittard, Proc. an-specific system.…”
Section: Cited By Oxendermentioning
confidence: 99%
“…Derepressed levels of this enzyme in fluorophenylalanineresistant transductants from either donor strain SG42 or SG32 confirmed that tyrR460 had been co-transduced with pyrF. In E. coli K-12, Im et al (14) found by transduction that tyrR showed about 4% linkage to trp and 13% linkage to pyrF. Brown and Somerville (3) found a higher frequency of linkage with their tyrR mutants.…”
Section: Resultsmentioning
confidence: 85%
“…Linkage of tyrR has been shown to both trp and pyrF in E. coli (3,14), whereas linkage could be established only to pyrF in Salmonella. However, the genome of bacteriophage P1 used in E. coli is larger than that of phage P22, and linkage may be obtained with genes that are not linked in Salmonella.…”
Section: Discussionmentioning
confidence: 99%